Complete genome assembly and functional characterization of Brucella melitensis strain IMHB1 from a clinical isolate in Inner Mongolia, China - Zheng, Xu; Liang, Chen; Shao, Liping; Liu, Chenfang; Yao, Ruiyuan; Peng, Li; Liang, Yanyu; Liang, Xiuwen; Liu, Shiyong (Frontiers in Cellular and Infection Microbiology, 2025)
Brucellosis is a globally prevalent zoonotic disease caused by Brucella species, posing a significant threat to both public health and the livestock industry. Despite ongoing research efforts, the mechanisms underlying Brucella pathogenesis remain poorly understood, particularly for strains isolated from specific geographical regions. A Brucella melitensis biotype III strain, IMHB1, was isolated from the blood culture of a patient in Hulunbuir, Inner Mongolia, China, who had experienced multiple relapses of brucellosis. Using Oxford Nanopore long-read sequencing, a complete 3.32 Mbp genome was assembled comprising two circular chromosomes with a GC content of 57.22% and 3,152 predicted coding sequences. Phylogenetic analysis revealed that IMHB1 was closely related to the cgST-588 type. Comprehensive genomic characterization identified mobile genetic elements, horizontally transferred regions, and prophage insertions. Functional annotation detected 10 genomic islands, 45 carbohydrate-active enzymes, 3 biosynthetic gene clusters, 4 antibiotic resistance genes, 20 eggNOG categories, and 252 KEGG pathways. Moreover, 66 predicted virulence factors and 18 experimentally verified proteins associated with pathogen-host interactions were identified, suggesting their potential roles in virulence and host adaptation. Based on extensive bioinformatics analysis, this study provides novel insights into the genomic characteristics and potential pathogenic mechanisms of Brucella melitensis strain IMHB1, enriching existing genomic resources and contributing to future research on brucellosis pathogenesis and therapeutic strategies.